Incidence and Outbreak of Healthcare-Onset Healthcare-Associated Clostridioides difficile Infections Among Intensive Care Patients in a Large Teaching Hospital in China - Li, Chunhui; Li, Yuan; Huai, Yang; Liu, Sidi; Meng, Xiujuan; Duan, Juping; Klena, John D.; Rainey, Jeanette J.; Wu, Anhua; Rao, Carol Y. (Frontiers in Microbiology, 2018)
Background: Clostridioides difficile infection (CDI) is an important cause of morbidity and mortality among hospitalized patients. In China, however, hospital staff do not routinely test for CDI, leading to under-diagnosis and poor patient outcomes. Locally generated CDI data can help assess the magnitude of the problem and strengthen approaches for CDI prevention and control. Methods: We prospectively monitored hospital-onset hospital-associated (HOHA) CDI in four intensive care units (ICUs) from June 2013 to September 2014 in a large teaching hospital in China. We collected clinical information from all ICU patients with >3 episodes of diarrhea occurring within a 24-hour period at least 48 hours following admission (suspect case definition). Stool specimens were collected from all suspect cases of CDI and cultured for C. difficile. Polymerase chain reaction (PCR) was used to detect toxin genes from positive isolates; multi-locus sequence typing (MLST) was used for typing and identifying novel strains. We estimated the incidence rate as the number of HOHA CDI cases per 10,000 patient days; 95% confidence intervals were generated to assess rate differences between the four ICUs. Results: A total of 593 hospital-onset diarrhea patients met the suspect case definition during the study period. Of these, 47 patients (8%) were positive for C. difficile and toxin genes. The HOHA-CDI incidence rate was 14.08 cases per 10,000 patient days (95% CI: 10.47-18.57). Six patients with HOHA CDI died. ST54 (n = 14, 20%) was the most common type of HOHA-CDI strain circulating in the hospital during the study period and was linked to a temporal cluster (outbreak) involving two (NICU and GICU) of the four ICUs. Conclusion: HOHA-CDI occurs among ICU patients at this teaching hospital, supporting the importance of routine testing for CDI. Information on strain distribution can help detect CDI outbreaks. Detection of ST54 strain in a temporal cluster suggests possible gaps in infection control practices that should be investigated and addressed as needed.